PICMET '09 - 2009 Portland International Conference on Management of Engineering &Amp; Technology 2009
DOI: 10.1109/picmet.2009.5261785
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging technology to diminish hostility in service recovery

Abstract: Since the most common causes for dissatisfaction in service recovery comes from service providers' hostility, we propose technology to be an efficient way to diminish hostility in service recovery. Unlike most researches to find the solution from the perspective of emotional labor, we discuss technology's benefits to emotional uncertainty. On the theoretical background of affective expectation model, C-O-P triangles, and emotional perspectives, we define the problem in service recovery and propose technology t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…also confirmed the impact of HT on the intention to use technologies such as smartphones and tablets for various activities [99], smart banking [100], internet marketing [101], mobile messaging [102], home digital services [103], and purchasing through online social networks [104]. These earlier findings have led us to believe the following: H12.…”
Section: Methods and Research Sample 31 Test Modelmentioning
confidence: 54%
See 2 more Smart Citations
“…also confirmed the impact of HT on the intention to use technologies such as smartphones and tablets for various activities [99], smart banking [100], internet marketing [101], mobile messaging [102], home digital services [103], and purchasing through online social networks [104]. These earlier findings have led us to believe the following: H12.…”
Section: Methods and Research Sample 31 Test Modelmentioning
confidence: 54%
“…Numerous studies have shown that PE has a positive and significant impact on the adoption of accessing electronic health records [93], learning in computer-supported classrooms [94], mobile app usage for digital wellness [95], mobile social network site usage by consumers [96], accessing social media by consumers [97], and the adoption and use of intermodal travel systems [98]. Other research on the intention to use internet or mobile technologies has confirmed the impact of PE on intention to use, such as for the use of smartphones and tablets for various activities [99], accessing technology that enables smart banking [100], marketing through the internet [101], mobile messaging [102], home digital services [103], and purchasing via social media platforms [104]. We suggest the following hypothesis: H6.…”
Section: Sustainable Development (Sd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Inter-and intra-organizational knowledge transfer [27] Inter-organizational knowledge transfer: Current themes and future prospects Inter-organizational knowledge transfer [24] Research on knowledge transfer in organizations: a morphology knowledge transfer [28] Knowledge communication and translation-a knowledge transfer model a knowledge transfer [37] Co-citation analysis of the scientific literature on innovation research traditions Diffusion of innovations and technology transfer [29] Antecedents and consequences of inter-organizational knowledge transfer: Emerging themes and openings for further research inter-organizational knowledge transfer [30] Knowledge management in strategic alliances: a review of empirical evidence Knowledge management [23] Subsidiary knowledge flows in multinational corporations: Research accomplishments, gaps, and opportunities knowledge flows Author (Year) Title Focus [38] A literature review with citation analysis of technology transfer Technology transfer [32] The evolving state-of-the-art in technology transfer research: Revisiting the contingent effectiveness model technology transfer [25] Technology, innovation, and knowledge: The importance of ideas and international connectivity Technology, innovation, and knowledge [26] Inter-organisational technology/knowledge transfer: a framework from critical literature review…”
Section: Author (Year)mentioning
confidence: 99%
“…Sustainability 2023, 15, x FOR PEER REVIEW 3 of 18 [37] Co-citation analysis of the scientific literature on innovation research traditions Diffusion of innovations and technology transfer [29] Antecedents and consequences of inter-organizational knowledge transfer: Emerging themes and openings for further research inter-organizational knowledge transfer [30] Knowledge management in strategic alliances: a review of empirical evidence Knowledge management [23] Subsidiary knowledge flows in multinational corporations: Research accomplishments, gaps, and opportunities knowledge flows [38] A literature review with citation analysis of technology transfer Technology transfer [32] The evolving state-of-the-art in technology transfer research: Revisiting the contingent effectiveness model technology transfer [25] Technology, innovation, and knowledge:…”
Section: Technology and Knowledge Transfermentioning
confidence: 99%